1997
DOI: 10.1074/jbc.272.21.13697
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Increases the Sensitivity of Islets of Langerhans for Inducible Nitric-oxide Synthase Expression Induced by Interleukin 1

Abstract: The purpose of this study was to evaluate the effects of interferon-␥ (IFN-␥) alone and in combination with interleukin 1␤ (IL-1␤) on inducible nitric-oxide synthase (iNOS) mRNA and protein expression, nitrite production, and insulin secretion by islets of Langerhans. Treatment of rat islets with IL-1␤ results in a concentration-dependent increase in the production of nitrite that is maximal at 5 units/ml. Individually, 0.1 unit/ml IL-1␤ or 150 units/ml rat IFN-␥ do not stimulate iNOS expression or nitrite pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
147
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(148 citation statements)
references
References 37 publications
1
147
0
Order By: Relevance
“…Inhibition of HDACs affects the NFκB-dependent production of iNOS and formation of NO IL-1β is known to induce expression of the gene encoding iNOS, an effect that is potentiated by IFNγ [18,34]. The subsequent formation of NO drives cell death by both necrosis and apoptosis, at least in rodent beta cells [35].…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of HDACs affects the NFκB-dependent production of iNOS and formation of NO IL-1β is known to induce expression of the gene encoding iNOS, an effect that is potentiated by IFNγ [18,34]. The subsequent formation of NO drives cell death by both necrosis and apoptosis, at least in rodent beta cells [35].…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously shown that, whereas IL-1 is a sufficient stimulus for the induction of iNOS mRNA expression and NO production in RIN cells, a combination of IL-1 and IFN-is required for the induction of NO formation by human islets (Cetkovic-Cvrlje and Eizirik, 1994;Eizirik et al, 1996;Heitmeier et al, 1997;Lortz et al, 2000). The increased toxicity of the cytokine combination compared with that of IL-1 alone (Figure 1) is attributable to a significantly higher rate of iNOS mRNA and protein expression (Figure 3) and subsequent NO production ( Figure Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…In their activated state, T-lymphocytes and macrophages, which are primary cellular components of islet insulitis, secrete high levels of IL-1 and IFN-, respectively. IL-1 alone, or in combination with TNFor IFN-, induces an excess production of nitric oxide (NO) by the iNOS in the pancreatic islets (Cetkovic-Cvrlje and Eizirik, 1994;Corbett and McDaniel, 1995;Heitmeier et al, 1997;Kwon et al, 2003a). Nitric oxide is a short-lived and highly reactive radical, which inhibits the Krebs-cycle enzyme aconitase and electron transport chain complexes I and II, resulting in reduced glucose oxidation rates, ATP generation, and insulin production (Welsh et al, 1991;Corbett et al, 1992;Cunningham and Green, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Protein samples were separated by SDS-PAGE and transferred to nitrocellulose membranes (Amersham Pharmacia Biotech) under semidry transfer conditions as previously described (43,44). Ab dilutions were: rabbit antimouse COX-2, 1/1000Ј rabbit anti-mouse iNOS, 1/1000; and HRP-conjugated donkey anti-rabbit, 1/7000.…”
Section: Western Blot Analysismentioning
confidence: 99%